Controlling management to deliver diversity and inclusion: Prospects and limits. (23rd November 2020) - Noon, Mike; Ogbonna, Emmanuel
Abstract: This study explores the attempts by executives in an organisation with a strategic business case for diversity and inclusion to close the equality implementation gap—between what is espoused and what is achieved—through greater control over managers in order to direct their actions towards pro‐diversity objectives, with a specific focus on gender and ethnicity in the internal human resource development processes. Drawing on agency theory and exploring data from interviews with executives and senior managers in an exemplar case study (the UK division of a multinational professional services organisation), the study shows how increased control through mandatory diversity training, diversity targets and diversity monitoring can push managers towards making progressive steps but is ultimately constrained by the need for management discretion. The actions and counter narratives by managers reveal the limits of control and expose tensions in an approach that combines attitudinal change with behavioural control. The agency of managers means the equality implementation gap can be reduced but never completely closed.